PERAN GURU DALAM MENYIAPKAN KOMPETENSI KERJA SISWA SESUAI TUNTUTAN DUNIA KERJA DI INDUSTRI BUSANA - Mally Maeliah (FTK Universitas Pendidikan Ganesha, 2010)
Teacher before starting the task as a teacher, he must first learn to understand all of theschool curriculum and education programs being implemented. Included should be known that isbuilding classrooms, libraries, study facilities, school equipment, teaching aids, and all the tools thatare useful for teachers. The success of education is not only determined by the accuracy of selectinga model curriculum design and implementation, but also by the completeness, quality andappropriateness of the use of education resources. Teachers can help enhance the completeness offacilities, media and resources to develop their own learning. In performing the duties of a teacherneeds to conduct cooperation with parents, with community agencies, and occasionally bring studentsto visit the objects that would need to know the students in the school curriculum framework. Besidescarrying out their professional duties in the school, the teacher shall also participate in communityactivities and improve the role and qualifications of the profession. The role of teachers in performingtheir duties as a lecturer and demonstrator, teacher as a good manager, and teacher as evaluator,that the process of evaluation is generally centered on the students.Key Words: Teacher, Competence, World of Work, Industrial Clothing